Programmed Recognition between Complementary Dinucleolipids To Control the Self‐Assembly of Lipidic Amphiphiles. Issue 5 (9th January 2020) - Morales‐Reina, Sara; Giri, Chandan; Leclercq, Maxime; Vela‐Gallego, Sonia; de la Torre, Isabel; Castón, José R.; Surin, Mathieu; de la Escosura, Andrés
Abstract: One of the major goals in systems chemistry is to create molecular assemblies with emergent properties that are characteristic of life. An interesting approach toward this goal is based on merging different biological building blocks into synthetic systems with properties arising from the combination of their molecular components. The covalent linkage of nucleic acids (or their constituents: nucleotides, nucleosides and nucleobases) with lipids in the same hybrid molecule leads, for example, to the so‐called nucleolipids. Herein, we describe nucleolipids with a very short sequence of two nucleobases per lipid, which, in combination with hydrophobic effects promoted by the lipophilic chain, allow control of the self‐assembly of lipidic amphiphiles to be achieved. The present work describes a spectroscopic and microscopy study of the structural features and dynamic self‐assembly of dinucleolipids that contain adenine or thymine moieties, either pure or in mixtures. This approach leads to different self‐assembled nanostructures, which include spherical, rectangular and fibrillar assemblies, as a function of the sequence of nucleobases and chiral effects of the nucleolipids involved. We also show evidence that the resulting architectures can encapsulate hydrophobic molecules, revealing their potential as drug delivery vehicles or as compartments to host interesting chemistries in their interior. Abstract : System evolution : A new type of nucleolipid is used in the context of systems chemistry to achieve control of the self‐assembly of lipidic amphiphiles, leading to different self‐assembled nano‐ and microstructures with potential as drug delivery vehicles or as compartments to host interesting chemistries in their interior.